Primary Blair Fusion in Displaced Comminuted Fracture Neck of Talus (Health Renaissance, 2011)
Background: Fracture-dislocation of the talus is one of the most severe injuries of the ankle. Opinion varies widely as to the proper treatment of this injury. Objective: To assess effectivness modifed blair technique-retention of the talar body white performing arthrodetis with anterion sliging grafl. Subjects and methods: It was an interventional prospective study. The cases & displaced tala necle fracture were included. They were treated using modifid Blair technique. The treatment and couses was anemed. Results: Tibiotalar fusion was acluwead is all the ankles at an average of 18 weeks. The results in 4 cut of 6 were encellent, and 2 had grand results. Conclusion: A good long-term result with tibiotalar arthrodesis with modification in blair technique was achived. Keywords: Anterior tibial sliding graft; arthrodesis; avascular necrosis of talus; Fracture dislocation of talus DOI: 10.3126/hren.v9i1.4357Health Renaissance, 2011: Vol.9 No.1:20-23